The Role of Image Inpainting Techniques in the Restoration of Artworks: An Evaluation and Comparative Study - Kucuk, Osman Furkan; Bar, Niyazi Furkan; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2024)
Cultural heritages represent crucial and distinctive facets of humanity's historical legacy. These structures possess intrinsic value in terms of their historical and artistic significance and function as tangible reflections of the identities and values embedded within societies. However, they are susceptible to deterioration over time, stemming from natural calamities or human-induced disturbances, underscoring the imperative of safeguarding and preserving cultural heritage. Alongside conventional restoration methodologies, contemporary approaches such as artificial intelligence (AI) and image-processing techniques have emerged as pivotal tools in cultural heritage restoration efforts. The burgeoning capabilities and advancements in image-processing technology have spurred scientists to intensify their endeavors in this domain. This study delves into the impact of image inpainting techniques on restoring artistic and cultural works. Several prominent models have been adeptly utilized in restoring obscured images, with an in-depth assessment of their performance and success metrics. Subsequently, the findings have been meticulously scrutinized and evaluated to ascertain their implications. © 2024 IEEE.
2nd International Conference on Sustaining Heritage, ICSH 2024 -- 29 September 2024 through 30 September 2024 -- Virtual, Online -- 205033
Keywords: cultural heritages; deep learning; inpainting; restoration